2020
DOI: 10.1177/2151459320912121
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Factors for Return to Prefracture Ambulatory Level in High Surgical Risk Elderly Patients Sustained Intertrochanteric Fracture and Treated With Proximal Femoral Nail Antirotation (PFNA) With and Without Cement Augmentation

Abstract: Introduction: Postoperative outcomes in the elderly patients with intertrochanteric fracture were generally poor with a low rate of return to prefracture ambulatory level (RPAL). Recent studies showed that proximal femoral nail antirotation (PFNA) with cement augmentation might be useful for postoperative functional recovery. This study aimed to compare the outcomes in elderly patients with high surgical risk, American Society of Anesthesiologist (ASA) grade 3 or 4, who sustained intertrochanteric fractures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
4
22
1
Order By: Relevance
“…A detailed description of the search and screening is shown in Fig 1 . Finally three observational studies [ 13 , 14 , 26 ] and four randomized controlled trials [ 12 , 15 , 27 , 28 ] fulfilled the criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the search and screening is shown in Fig 1 . Finally three observational studies [ 13 , 14 , 26 ] and four randomized controlled trials [ 12 , 15 , 27 , 28 ] fulfilled the criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Thromboembolic complications included all venous thrombembolisms in the follow-up period and are listed as a part of systemic complication as well as separately [ 12 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of PFNA include the following: avoid the instability of the proximal femur after internal fixation; conducive to fracture healing; and reduce the incidence of hip varus deformity. [ 32 ] Zhou et al [ 26 ] reported that hip joint function of patients is effectively improved after surgical treatment, which significantly reduces the incidence of post-operative complications. Based on the above advantages, PFNA is suitable for elderly patients with partial intertrochanteric fractures because this treatment requires low surgical tolerance.…”
Section: Discussionmentioning
confidence: 99%